1990
DOI: 10.1073/pnas.87.7.2385
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mouse mammary tumor proviral DNA and protooncogene expression: association with nutritional regulation of mammary tumor development.

Abstract: Chronic energy intake restriction (CEIR) reduces mouse mammary tumor virus (MMTV)-induced mammary tumors in C3H/Ou mice. Fewer than 10% of C3H/Ou mice developed mammary tumors during 88 wk of study when subjected to CEIR regardless of calorie source (fat vs. carbohydrate). By contrast, 100% of mice fed ad libitum diets relatively high in fat or carbohydrate or a commercial diet developed tumors by 35-40 wk. MMTV proviral DNA transcription was shown to be activated in spleen, liver, lung, kidney, small intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
1
29
0
4
Order By: Relevance
“…ICR mice had the lowest tumor incidence and number of MTs per tumor-bearing mouse. Furthermore, these findings are consistent with several earlier publications, which reported that intermittent fasting/refeeding interventions prevented spontaneous MT development in rodents (46,(48)(49)(50). Somewhat different results have been reported for the consequences of ICR interventions using chemical carcinogen models when the feeding regimen is initiated at the time of carcinogen administration.…”
Section: Discussionsupporting
confidence: 82%
“…ICR mice had the lowest tumor incidence and number of MTs per tumor-bearing mouse. Furthermore, these findings are consistent with several earlier publications, which reported that intermittent fasting/refeeding interventions prevented spontaneous MT development in rodents (46,(48)(49)(50). Somewhat different results have been reported for the consequences of ICR interventions using chemical carcinogen models when the feeding regimen is initiated at the time of carcinogen administration.…”
Section: Discussionsupporting
confidence: 82%
“…The other studies used purified 20,22,35,36 or semi-purified diets. 21,23,24,42 Given the strong and consistent effect of energy restriction on cancer prevention in experimental animals, it is clearly possible that the balance between energy consumption, retention and expenditure, perhaps in combination with frequency and length of fasting periods between meals, represents an underlying and central link in the relationship between diet, nutrition and cancer in Western society. 43 Future dietary cohort studies and intervention trials are needed to get insight into the effects of energy and/or fat restriction on human breast cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that CEIR can modulate mouse mammary tumor virus (MMTV) proviral expression at the mRNA level, delay protooncogene activation, and abrogate the development of breast tumors (6,14,15). In the current study, we show that the protective influences of CEIR can be imposed in an organ site of retrovirus-induced tumorigenesis other than the breast by demonstrating that calorie restriction can significantly impair retrovirus-induced lymphomagenesis in AKR mice.…”
mentioning
confidence: 99%
“…The preparation and composition of the two semipurified diets used have been described in detail (6,14) (Table 1). All dietary constituents were obtained from ICN.…”
mentioning
confidence: 99%
See 1 more Smart Citation